2004
DOI: 10.1111/j.1601-5223.2001.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation in the Elymus dahuricus complex (Poaceae): evidence from grain proteins, DNA, and crossability

Abstract: The status of the taxa Elymus dahuricus Turcz. ex Griseb., E. excelsus Turcz. ex Griseb., E. woroschilowii Probat. and E. tangutorum (Nevski) Hand.-Mazz., all of which are sometimes treated as members of E. dahuricus s.l. or as constituting the E. dahuricus complex, has been investigated using morphological, biochemical (SDS-PAGE of endosperm proteins) and molecular (DNA-AFLP) variation characteristics. Populations include accessions from Siberia, Far East (Russia), Tien-Shan (Kirghizstan), and Tibet and Sichu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
1
15
0
1
Order By: Relevance
“…Taxonomic treatment of E. tangutorum Elymus tangutorum differs from E. dahuricus by its spikelets disposition slightly secund, shorter glume awn, and shorter lemma awn (Baum et al, 2011). Subtle morphological differences resulted in different taxonomic treatments of the E. dahuricus complex (Peschkova, 1985(Peschkova, , 1990Probatova, 1985;Czerepanov, 1995;Agafonov et al, 2001;Baum et al, 2011 (Brysting et al, 2000). It was reported that intergenomic rearrangements could be affected by the environment (Wang et al, 2012(Wang et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Taxonomic treatment of E. tangutorum Elymus tangutorum differs from E. dahuricus by its spikelets disposition slightly secund, shorter glume awn, and shorter lemma awn (Baum et al, 2011). Subtle morphological differences resulted in different taxonomic treatments of the E. dahuricus complex (Peschkova, 1985(Peschkova, , 1990Probatova, 1985;Czerepanov, 1995;Agafonov et al, 2001;Baum et al, 2011 (Brysting et al, 2000). It was reported that intergenomic rearrangements could be affected by the environment (Wang et al, 2012(Wang et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Всего было получено 85 гибрид-ных растений F 1 в 35 комбинациях скрещивания. Все процедуры по созданию половых гибридов, оценке их семенной фертильности (СФ) и уров-ней половой совместимости биотипов Cs были выполнены, как описано ранее (Agafonov, 1997;Agafonov et al, 2001;Lu, Bothmer, 1990). Анализ репродуктивных свойств и морфологических особенностей гибридных особей в поколениях проводили на особях, выращенных на открытых делянках Центрального сибирского ботаниче-ского сада СО РАН (г. Новосибирск).…”
Section: материалы и методыunclassified
“…Cytology: 2 n = 6 x = 42 (Probatova, 1978; Probatova & Sokolovskaya, 1982). Genome StStHHYY (Agafonov et al, 2001).…”
Section: Taxonomic Treatmentmentioning
confidence: 99%